Fermentation by Probiotic Lactobacillus gasseri Strains Enhances the Carotenoid and Fibre Contents of Carrot Juice - Xu, Yue (Foods, 2020)
Carrot juice (straight, 8.5 Brix and concentrated, 15.2 Brix) was fermented by lactic acid bacteria (Lactobacillus gasseri strain DSM 20604 or DSM 20077). Fermentation enhanced the nutritional profile of carrot juice. There was a greater sugar reduction (27%) in fermented straight carrot juices than in the fermented concentrated juices (15%). The sugar reduction was independent of the strain used for fermentation. The two L. gasseri strains synthesised fructosyltransferase enzymes during fermentation of carrot juice samples that enabled conversion of simple sugars primarily into polysaccharides. The level of conversion to polysaccharides was dependent on the L. gasseri strain and juice concentration. Fermentation of carrot juice by L. gasseri enables the production of a nutritionally-enhanced beverage with reduced calorie and prebiotic potential. An additional benefit is the increased carotenoid content observed in straight and concentrated juices fermented by Lactobacillus gasseri DSM 20077 and the concentrated juice fermented by Lactobacillus gasseri DSM 20604.